Slang Words Used in Dope Movie - Hanifa Fildza Ghassani; Otong Setiawan Djuharie; Toneng Listiani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the types and meanings of slang words used in Rick Famuyiwa's "Dope" movie (2015), and the research addresses the gap in understanding community-specific communication patterns by analysing authentic teenage dialogue through the theoretical framework for slang classification proposed by Allan and Burridge (2006). This study used qualitative descriptive methodology to identify and categorise slang expressions from the film's dialogue and transcript. The analysis identified 91 slang words, which were classified into five types: flippant, fresh and creative, imitative, clipping, and acronym. Flippant, fresh and creative slang indicates that characters use language that is innovative and different from standard meanings, reflecting the dynamic nature of urban youth communication. Slang is employed to establish interpersonal relationships, create group identities and express emotions. The findings contribute to an understanding of how slang is used in media representations, enriching the knowledge of youth culture and its application in film.